Numerical Analysis of Transfer of Heat by Forced Convection in a Wavy Channel - Naseer Abboodi Madlool; Mohammed J Alshukri; Ammar I Alsabery; Adel A Eidan; Ishak Hashim (International Journal of Renewable Energy Development, 2023)
Convective heat transfer of laminar forced convection in a wavy channel is studied in this paper. Numerical simulations of the 3D steady flow of Newtonian fluid and heat transfer characteristics are obtained by the finite element method. The effects of the Reynolds number (10 ≤Re≤1000), number of oscillations (0 ≤N≤5) and amplitude of the wall (0.05 ≤A≤0.2) on the heat transfer have been analyzed. The results show that the average Nusselt number is elevated as the Reynolds number is raised, showing high intensity of heat transfer, as a result of the intensified effects of the inertial and zones of recirculation close to the hot wavy wall. The rate of heat transfer increases about 0.28% with the rise of the number of oscillations. In the transfer of heat along a wavy surface, the number of oscillations and the wave amplitude are important factors. With an increment in the number of oscillations, the maximal value of the average velocity is elevated, and its minimal value occurs when the channel walls are straight. The impact of the wall amplitude on the average Nusselt number and dimensionless temperature tends to be stronger compared to the impact of the number of oscillations. An increase of the wall amplitude improves the rate of heat transfer about 0.91% when the Reynolds number is equal 100. In addition, when the Reynolds number is equal 500, the rate of heat transfer grows about 1.1% with the rising of the wall amplitude.